Engineering a Highly Regioselective Fungal Peroxygenase for the Synthesis of Hydroxy Fatty Acids - Gomez de Santos, Patricia; González‐Benjumea, Alejandro; Fernandez‐Garcia, Angela; Aranda, Carmen; Wu, Yinqi; But, Andrada; Molina‐Espeja, Patricia; Maté, Diana M.; Gonzalez‐Perez, David; Zhang, Wuyuan; Kiebist, Jan; Scheibner, Katrin; et al. (Angewandte Chemie International Edition, 2023)
The hydroxylation of fatty acids is an appealing reaction in synthetic chemistry, although the lack of selective catalysts hampers its industrial implementation. In this study, we have engineered a highly regioselective fungal peroxygenase for the ω‐1 hydroxylation of fatty acids with quenched stepwise over‐oxidation. One single mutation near the Phe catalytic tripod narrowed the heme cavity, promoting a dramatic shift toward subterminal hydroxylation with a drop in the over‐oxidation activity. While crystallographic soaking experiments and molecular dynamic simulations shed light on this unique oxidation pattern, the selective biocatalyst was produced by Pichia pastoris at 0.4 g L−1 in a fed‐batch bioreactor and used in the preparative synthesis of 1.4 g of (ω‐1)‐hydroxytetradecanoic acid with 95 % regioselectivity and 83 % ee for the S enantiomer. The biocatalytic hydroxylation of fatty acids is an appealing reaction, but the generation of over‐oxidation by‐products and the lack of selectivity hampers its transfer to industry. Now a highly selective and efficient peroxygenase has been engineered for the production of hydroxy fatty acids through a synthetic procedure that can be rapidly adapted to the preparative scale.